2017
DOI: 10.1007/s00268-017-4323-x
|View full text |Cite
|
Sign up to set email alerts
|

Surgery for Primary Hyperparathyroidism with Normal Non‐suppressed Parathyroid Hormone can be Both Challenging and Successful

Abstract: Parathyroidectomy can have a high cure rate in the context of normal PTH levels despite an increased likelihood of negative imaging and multigland resection. Operative success is equivalent to classic PHPT when PTH levels are > 55 pg/mL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 29 publications
(26 reference statements)
1
10
0
Order By: Relevance
“…Our earlier work investigated the effect of biochemical profile on IOPTH and demonstrated a slower rate of IOPTH decline in NC 25,26 and NH 27 patients compared with typical profile patients. Surgical resection of adenomatous glands has been demonstrated to be beneficial in both NC 28e30 and NH 31 groups. In detailed analyses of long-term cure with respect to IOPTH criteria, Trinh et al 26 demonstrated comparable outcomes for NC patients as long as a >50% IOPTH decrease was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Our earlier work investigated the effect of biochemical profile on IOPTH and demonstrated a slower rate of IOPTH decline in NC 25,26 and NH 27 patients compared with typical profile patients. Surgical resection of adenomatous glands has been demonstrated to be beneficial in both NC 28e30 and NH 31 groups. In detailed analyses of long-term cure with respect to IOPTH criteria, Trinh et al 26 demonstrated comparable outcomes for NC patients as long as a >50% IOPTH decrease was achieved.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, there may be an increasing rate of operations for patients with mild disease such as those with normal non-suppressed parathyroid hormone levels which is known to correlate with increased likelihood of negative imaging and MG resection. 17 In our series, 6 patients had an unsuccessful operation with documented persistence of postoperative hypercalcemia. All of these cases started with a focused exploration at the most obvious site of disease and then 5 of the cases were converted to a bilateral exploration due to an inadequate drop in IOPTH.…”
Section: Discussionmentioning
confidence: 68%
“…These patients are more likely to have negative imaging, multiglandular disease, and a PTH decline that does not meet standard curative criteria. 19 Only 75 per cent of patients with normal PTH levels will have a 50 per cent decline, and cure rates are less (88% vs 96%). 19 There may be a subset of these patients in whom the diagnosis is equivocal.…”
Section: Discussionmentioning
confidence: 99%
“…19 Only 75 per cent of patients with normal PTH levels will have a 50 per cent decline, and cure rates are less (88% vs 96%). 19 There may be a subset of these patients in whom the diagnosis is equivocal. These are challenging patients at a primary operation, and perhaps patients should be further classified based on postoperative risk of failure and follow-up tailored accordingly.…”
Section: Discussionmentioning
confidence: 99%